The effects of cessation of supplementary isokinetic and isotonic training on strengh and biomechanical variables in state-level weightlifters - Mohamed, Iqbal Wan (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2016)
INTRODUCTION: To date, no studies have been carried out to compare the effects of cessation of supplementary Isokinetic Training (IT) and Isotonic Training (TON) in strength and biomechanical variables among elite weightlifters. Regarding biomechanical variables of the rotator cuff muscles, most studies were conducted on sedentary population and racket-sports instead of advanced level of weightlifting athletes. OBJECTIVES: This study aimed to compare the cessations effects 1 month after they completed the 24 sessions of isokinetic and isotonic supplementary training among state-level weightlifters on biomechanical variables of rotator cuff muscles. METHODS: Nineteen participants were gender- and weight- matched and randomly assigned into isotonic training group (TON) and isokinetic training (IT) group. Both groups went through 24 sessions of training programmed three times per week for 8 weeks in three distinct lifting positions. The intensity of training was increased progressively in terms of number of lifting repetitions per set and number of sets lifted. After 1 month of the cessation of supplementary training programmed, the athlete when through a follow-up testing. The 2D-kinematic analysis of barbell velocity was evaluated during the second pull and turnover phases of I-RM power clean and power snatch tests. In IT group, the participant was allowed to be seated on the the guidelines instructions. The position of the chair and dynamometer will be set at the particular angle depends on the chair to perform the training programed based on the